KERJASAMA GURU BIMBINGAN DAN KONSELING DENGAN ORANG TUA SISWA DALAM MENGATASI PERILAKU SEKS DI SMA TUNAS BANGSA DI KELAS XI DI KABUPATEN ROKAN HILIR - Meri Syafitri; Dodi Pasila Putra (STKIP Subang, 2025)
This study originated from problems frequently encountered by students in the school environment. At Tunas Bangsa High School, there are still students who have problems with their sexual behavior. For example, there are students who hold hands in the school environment, hug each other in the classroom during detention, touch sensitive parts of the body as a joke, and kiss the hands of the opposite sex. This study aims to: identify the forms of cooperation between guidance counselors and parents in addressing sexual behavior. Cooperation between guidance counselors and parents is important to establish a shared perception between the school, guidance counselors, and parents in addressing sexual behavior. This study aims to identify: 1. The forms of cooperation between guidance counselors and parents in addressing sexual behavior. 2. The obstacles in cooperation between guidance counselors and parents in addressing sexual behavior. 3. The efforts made by guidance counselors and parents to identify the obstacles that occur in cooperation between guidance counselors and parents in addressing sexual behavior. This study uses qualitative research methods, namely describing events that occur in the field. This study was conducted at Tunas Bangsa High School in Rokan Hilir Regency as a place to find symptoms or phenomena that will be studied. There are two informants in this study, namely the key informant, the guidance counselor at Tunas Bangsa High School, and supporting informants, namely students and parents. The data collection techniques used were observation and interviews. The data analysis technique in this study was to examine all data, reduce data, and display it. To ensure the validity of the data, this study used three triangulation techniques, namely source, method, and time. The most widely used triangulation technique was the source technique. The results of this study are: 1. The form of cooperation between the guidance counselor and parents in addressing sexual behavior is communication, namely formal and informal communication and parental involvement. 2. The obstacles that occur in the cooperation between the guidance counselor and parents in addressing sexual behavior. 3. Efforts made by the school to address sexual behavior in the collaboration between guidance counselors and parents in addressing sexual behavior: a. The school provides the best services to students. b. Guidance counselors align perceptions and values instilled by the school.